Conservative treatment in the management of mandibular fractures in children: a scope review protocol (Research, Society and Development, 2022)
Maxillofacial fractures in pediatric patients are of rare occurrence and mostly affect the mandibular bone. Mandibular fractures can be characterized as severe, depending on the location and mode of presentation, resulting in several complications due to damage to dental germs and facial development of the child. Thus, conservative treatment has been frequently adopted in order to minimize the complications and morbidity of patients. The objective of this protocol is to present methodological steps to perform a scope review, in order to explore the aspects of choosing conservative treatment for the management of mandibular fractures in children, mapping and stumarizing the evidence regarding the prevalence and characteristics of the most recurrent lesions due to the condition studied, in addition to verifying how this theme has been conducted in the studies and identifying the possible gaps in the literature. This protocol was developed according to the guidelines of the Joanna Briggs Institute Manual and registered in the Open Science Framework. PubMed databases via MEDLINE, Web of Science, SciVerse Scopus (Elsevier), LILACS via VHL and Google Scholar will be used to search and select the studies. The data will be extracted and presented in the form of frames and/or images and descriptively, following the guidelines of the PRISMA-ScR checklist. This protocol may allow a scope review, with consistent methodology and, from it, to obtain a greater knowledge about the benefits of conservative therapy for the treatment of mandibular fractures in children, expanding the view one has on the subject.